Analysis of Mathematics Learning Difficulties in Terms of Students Cognitive Styles at Madrasah Aliyah Laboratory Jambi City - Akbar Mulyawan Nugraha; Muslimahayati Muslimahayati; Sunarto Sunarto (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2025)
This research aims to test the effectiveness of cognitive style on students' mathematics learning difficulties at the Jambi City Laboratory Madrasah Aliyah and obtain the results of an analysis of mathematics learning difficulties in terms of cognitive style. This research is a type of qualitative research with a descriptive approach. This research was conducted at the Madrasah Aliyah Laboratory in Jambi. The research subjects were 24 students in class XI Science 1 Madrasah Aliyah Laboratory Jambi City. Data collection techniques used the GEFT test (Group Embedded Figure Test), interviews, and observation. The results of this research are (1) Students with a field dependent cognitive style are 14 subjects out of 24 students who tend to have difficulty breaking down complex information into simpler parts and experience obstacles in determining problem solutions independently, (2) Students with a field independent cognitive style are 10 subjects out of 24 students who have better abilities in understanding, planning and solving problems compared to field dependent students. Apart from that, they also tend to think analytically until they get the right results. (3) The results of interviews with students indicate that students with a field independent cognitive style tend to be superior in identifying hidden patterns and solving problems based on visual analysis, while students with a field dependent cognitive style need more contextual learning strategies and clearer visualization assistance.